2010
DOI: 10.1016/j.amjcard.2010.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Relation of QRS Width in Healthy Persons to Risk of Future Permanent Pacemaker Implantation

Abstract: In the setting of acute myocardial infarction, prolongation of the QRS interval on an electrocardiogram identifies patients at risk of needing permanent pacemaker implantation. However, the implications of a prolonged QRS in healthy individuals are unclear, especially since the QRS prolongation encountered in this setting is typically mild. We studied the relation between QRS duration and incident pacemaker implantation in a community-based cohort of 8,311 individuals (mean age 54 years, 55% women) who attende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
9
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 24 publications
3
9
1
Order By: Relevance
“…This is in contrast to a study by Cheng et al that showed that when physician-derived and computer-derived QRS durations were available on the same ECGs, the correlation between techniques was high (r=0,81, p<0.001) 20. They measured ‘to the end of the R or S wave’—an end that in our experience is hard to define when it is slurred, notched, depressed or elevated.…”
Section: Discussioncontrasting
confidence: 80%
“…This is in contrast to a study by Cheng et al that showed that when physician-derived and computer-derived QRS durations were available on the same ECGs, the correlation between techniques was high (r=0,81, p<0.001) 20. They measured ‘to the end of the R or S wave’—an end that in our experience is hard to define when it is slurred, notched, depressed or elevated.…”
Section: Discussioncontrasting
confidence: 80%
“…We replicated similar results to the prior analyses: first-degree atrioventricular block (HR, 15 This study demonstrated that first-degree atrioventricular block and left bundle branch block, but not right bundle branch block, increased the risk of developing complete atrioventricular block in a large general population, consistent with the previous studies [6][7][8][9]. Structural heart disease is one of the major causes of advanced conduction disease and there is the possibility that our results were driven by concomitant heart disease [13,14].…”
supporting
confidence: 89%
“…A recent community-based cohort study showed that first-degree atrioventricular block is associated with the future need for pacemaker implantation and all-cause mortality [6]. Furthermore, the prolongation of QRS duration and bundle branch block have also been associated with cardiovascular events [7][8][9]. Here, we studied the association of common electrocardiographic findings frequently encountered in clinical practice with the risk of developing complete (third-degree) atrioventricular block in the general population.…”
mentioning
confidence: 98%
“…Models were first adjusted for age and sex and further adjusted for systolic blood pressure (BP), use of antihypertensive medications, body mass index (BMI), diabetes mellitus, smoking status, physical activity index, valvular heart disease, ECG left ventricular hypertrophy, total-to-HDL cholesterol ratio, minor cardiovascular disease (angina, transient ischemic attack, and intermittent claudication), PR interval, and QRS duration. 23,24 To account for multiple hypothesis testing (7 outcomes), a Bonferroni-corrected P-value of <0.007 was considered significant for primary analyses. We tested for proportionality of hazards for each outcome by fitting an interaction term of follow-up time and heart rate and by visually checking Martingale-based residuals.…”
Section: Discussionmentioning
confidence: 99%
“…Separate analyses were conducted for incident cardiovascular disease, heart failure, stroke, coronary heart disease, pacemaker implantation, all‐cause death, and cardiovascular death. Models were first adjusted for age and sex and further adjusted for systolic blood pressure (BP), use of antihypertensive medications, body mass index (BMI), diabetes mellitus, smoking status, physical activity index, valvular heart disease, ECG left ventricular hypertrophy, total–to–HDL cholesterol ratio, minor cardiovascular disease (angina, transient ischemic attack, and intermittent claudication), PR interval, and QRS duration . To account for multiple hypothesis testing (7 outcomes), a Bonferroni‐corrected P ‐value of <0.007 was considered significant for primary analyses.…”
Section: Methodsmentioning
confidence: 99%